2021
DOI: 10.1371/journal.pone.0254858
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram of age-specific anti-Müllerian hormone levels in healthy Egyptian females

Abstract: Background Anti-Müllerian hormone (AMH) is an important determinant of ovarian reserve in fertility workups in many clinical settings. Thus, we investigated the age dependent decline in AMH specific to the Egyptian population and sought to establish an age dependent reference interval parametrically. Methods Serum samples were collected from 841 apparently healthy women. AMH was measured using an electro-chemiluminescent technique. Box-Cox power transformation was used to make the AMH distribution Gaussian f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
8
1
Order By: Relevance
“…Bleil, et al [17], using the Beckman Coulter ELISA, found that Hispanic women had lower AMH concentrations across all ages, whereas African-American and Chinese women had lower AMH concentrations only at younger (i.e., 25 and 30 years) and middle ages (i.e., 30, 35, and 40 years), respectively, than Caucasian women. In a recent study using the Elecsys assay in Egyptian women, the AMH concentrations across all ages were lower than those in our study or the manufacturer-provided values based on Caucasian populations [12]. In our study, the median AMH concentrations in Korean women of 19-34 years were slightly higher than those shown in the package insert.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…Bleil, et al [17], using the Beckman Coulter ELISA, found that Hispanic women had lower AMH concentrations across all ages, whereas African-American and Chinese women had lower AMH concentrations only at younger (i.e., 25 and 30 years) and middle ages (i.e., 30, 35, and 40 years), respectively, than Caucasian women. In a recent study using the Elecsys assay in Egyptian women, the AMH concentrations across all ages were lower than those in our study or the manufacturer-provided values based on Caucasian populations [12]. In our study, the median AMH concentrations in Korean women of 19-34 years were slightly higher than those shown in the package insert.…”
Section: Discussioncontrasting
confidence: 88%
“…As the 40-44 years, 45-49 years, and 50-54 years age groups exhibited extreme distribu-diabetes mellitus, or hypercholesterolemia, and (4) availability of serum and DNA samples. The participants were divided into seven 5-year age groups: 19-24 years, 25-29 years, 30-34 years, 35-39 years, 40-44 years, 45-49 years, and 50-54 years [7,[10][11][12]. There was a minimum of 120 participants in each group.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, automated assays have been developed, and these yield lower AMH levels than ELISA [ 6 , 7 ]. Therefore, it is necessary to establish a reference interval suitable for the new test method [ 8 - 10 ].…”
mentioning
confidence: 99%